2018
DOI: 10.12659/msm.907798
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fibroblast Growth Factor 5 (FGF5) and Its Influence on Survival of Breast Cancer Patients

Abstract: BackgroundThe clinical outcome of patients with breast cancer (BC) remains poor.Material/MethodsWe analyzed BC microarray studies GSE37751, GSE7390, and GSE21653 to investigate the expression of FGF5 gene between BC patients and their normal counterparts and the relationship between FGF5 expression and age, tumor size, histopathological grading, estrogen receptors, clinical risk group according to St Gallen criteria, clinical risk group according to NPI criteria, clinical risk group according to Veridex signat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…It is suggested that FGF5 may be a promising treatment strategy for NSCLC. Furthermore, overexpression of FGF5 has also been revealed to contribute to malignant development in several other human tumors, such as osteosarcoma, melanoma and breast cancer ( 23 25 ). Similarly, in the present study, FGF5 played a role in the promotion of the malignant development of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that FGF5 may be a promising treatment strategy for NSCLC. Furthermore, overexpression of FGF5 has also been revealed to contribute to malignant development in several other human tumors, such as osteosarcoma, melanoma and breast cancer ( 23 25 ). Similarly, in the present study, FGF5 played a role in the promotion of the malignant development of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al have demonstrated that the downregulation of FGF5 inhibited cell growth and invasion of human non-small-cell lung cancer cells 9 . FGF5 expression was found to be significantly upregulated in breast cancer patients relative to that in normal controls ( P < 0.0001), and breast cancer patients in the FGF5 low-expression group were correlated with better clinical characteristics 10 . Despite these findings in and the proposed tumor-promoting role of FGF5 in other malignancies, FGF5 has not been further investigated in PTC so far.…”
Section: Introductionmentioning
confidence: 92%
“…FGF5 is overexpressed in breast cancer tissue. 608 Guo et al 609 reported that FGF6 was significantly decreased in non-metastatic liver cancer lesion tissues and increased in metastatic liver carcinoma tissue. FGF7 is expressed in normal mucosal gland epithelium and in stromal fibroblasts, and FGF7 protein levels were elevated in gastric inflammation and gastric adenocarcinoma.…”
Section: Fgf Signaling In Tumorsmentioning
confidence: 99%